Strength properties and temperature of C55/67 concrete prepared with various types of cement - Chin, Kah Heng (2024)
The evolution of concrete technology has introduced numerous cement types, each with unique compositions affecting concrete properties, making the selection of the appropriate cement critical for achieving desired results, especially in civil engineering applications. The research addresses the feasibility of substituting different cements without compromising the desired strength, particularly in ready-mix concrete scenarios where material shortages may occur. This study explores the influence of various cement types on the properties of C55/67 concrete, with specific aims to achieve the design strength at 28 days, and to examine the fresh and mechanical properties, as well as the temperature characteristics of the concrete. It also considers concrete mix design methodologies tailored to specific cement types to ensure optimal performance and quality in diverse environmental conditions, with a particular focus on enhancing concrete quality and reliability in water-retaining structures where crack prevention is paramount. The study's trial mix, using control mix of OPC 42.5N, achieved the desired slump value (60-180 mm) and a compressive strength of 67 MPa at 28 days, making it the basis for the actual mix application. In actual mix, test results indicated that OPC 42.5N exhibited the highest workability, followed by OPC 52.5N, PLC 32.5N, and PFA 32.5N, in that order. This sequence was consistent for the hardened density of the concrete. PFA 32.5N had the shortest initial setting time. For compressive strength, OPC 42.5N demonstrated the highest strength, with OPC 52.5N following, and PFA 32.5N and PLC 32.5N trailing at both 7 and 28 days. By 56 days, OPC 52.5N showed a slightly higher compressive strength than OPC 42.5N, while PLC 32.5N and PFA 32.5N remained lower than those of concrete prepared with OPC cements. Temperature tests revealed that PLC 32.5N reached its peak temperature the quickest, followed by OPC 52.5N, PFA 32.5N, and OPC 42.5N. However, OPC 52.5N reached a significantly higher peak temperature than the others, followed by PLC 32.5N, OPC 42.5N, and PFA 32.5N. Overall, OPC 42.5N showed the best performance across workability, strength, and temperature tests, making it the preferred choice for ensuring concrete quality and reliability in various environmental conditions.